Strategy of Bekangdam Jaya in Logistic Distribution for Flood Disaster Mitigation in Jakarta Region 2020-2025 - Zakaria, Zakaria; Hipdizah, Hipdizah; Asmoro, Novky (Yayasan Meira Visi Persada, 2026)
Flood disaster management in DKI Jakarta demands a rapid, precise, and coordinated logistics distribution strategy. As the center of government and economy, paralysis due to flooding in Jakarta has a systemic impact. Bekangdam Jaya, as a support unit of Kodam Jaya, plays a strategic role in supporting the Regional Government through the provision of infrastructure, personnel mobilization, and aid distribution during emergency response, in accordance with the mandate of Law Number 34 of 2004 concerning the TNI. The problem in this research is how Bekangdam Jaya's strategy in distributing logistics for flood disaster management in the Jakarta area. This study aims to analyze the capability of facilities and infrastructure (Means), the effectiveness of operational distribution (Ways), and to formulate a strategy for optimizing logistics distribution (Ends) using the Arthur F. Lykke Jr. strategy framework. The research method used is qualitative with a case study design. Data was collected through in-depth interviews with informants from Bekangdam Jaya and BPBD DKI Jakarta, field observations, and analysis of related documents. The results show that Bekangdam Jaya has strong logistics capabilities, including a transport fleet, rubber boats, field kitchens, and trained personnel. However, the effectiveness of distribution is still hampered by inter-agency coordination constraints, the accuracy of dynamic logistics needs data, and accessibility challenges in flooded areas. The discussion emphasizes the gap between potential capabilities and their realization in the field due to coordination friction and information systems. Optimization of the logistics distribution strategy requires strengthening civil-military interoperability through the refinement of joint Standard Operating Procedures (SOPs), the implementation of an integrated data system for real-time information management, and the decentralization of logistics by pre-positioning in flood-prone areas. With a strategy that is aligned between Ends, Ways, and Means, the effectiveness of the disaster logistics response can be increased, thereby supporting the acceleration of handling flood victims in Jakarta